STRATEGI KOMUNIKASI GURU DALAM PEMBELAJARAN PAI DI DESA GUNUNG BESAR KECAMATAN ABUNG TENGAH LAMPUNG UTARA - Iin Novitasari; Chairul amriyah; Sovia Mas Ayu (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
Teacher Communication Strategy in PAI Learning in Gunung Besar Village, Central Abung District, North Lampung 1. Communication is one of the daily activities that is truly connected to all human life, as well as in Islamic Religious Education learning requires strategies so that learning is achieved and communication requires appropriate strategies so that learning is achieved and this research is to describe PAI teachers' strategies in learning at the elementary school in Gunung Besa village, Abung Tengah sub-district, North Lampung. The objectives of this research are 1) Describe the communication strategies of PAI teachers in PAI learning in Gunung Besar Village, Abung Tengah District, North Lampung 2) Describe the various communication strategies applied by PAI teachers in learning in Gunung Besar Village, Abung Tengah District, North Lampung 3) Describe analysis of teacher communication strategies in PAI learning in Gunung Besar village, Abung Tengah sub-district, North Lampung. This research uses a qualitative approach with a case study type of research. Data collection uses interviews, observation, documentation and tests, while data analysis applies descriptive qualitative. This research produces the following conclusions. First, the process of introducing communication strategies shows two things: 1) verbal communication strategies which include strategies for giving messages and advice, guiding strategies 2) non-verbal communication strategies strategies for persuading or inviting.